The functional role of microRNAs in alcoholic liver injury. Issue 2 (8th January 2014) - McDaniel, Kelly; Herrera, Leonardo; Zhou, Tianhao; Francis, Heather; Han, Yuyan; Levine, Phillip; Lin, Emily; Glaser, Shannon; Alpini, Gianfranco; Meng, Fanyin
Abstract The function of microRNAs (miRNAs) during alcoholic liver disease (ALD) has recently become of great interest in biological research. Studies have shown that ALD associated miRNAs play a crucial role in the regulation of liver‐inflammatory agents such as tumour necrosis factor‐alpha (TNF‐α), one of the key inflammatory agents responsible for liver fibrosis (liver scarring) and the critical contributor of alcoholic liver disease. Lipopolysaccharide (LPS), a component of the cell wall of gram‐negative bacteria, is responsible for TNF‐α release by Kupffer cells. miRNAs are the critical mediators of LPS signalling in Kupffer cells, hepatocytes and hepatic stellate cells. Certain miRNAs, in particular miR‐155 and miR‐21, show a positive correlation in up‐regulation of LPS signalling when they are exposed to ethanol. ALD is related to enhanced gut permeability that allows the levels of LPS to increase, leads to increased secretion of TNF‐α by the Kupffer cells and subsequently promotes alcoholic liver injury through specific miRNAs. Meanwhile, two of the most frequently dysregulated miRNAs in steatohepatitis, miR‐122 and miR‐34a are the critical mediators in ethanol/LPS activated survival signalling during ALD. In this review, we summarize recent findings regarding the experimental and clinical aspects of functions of specific microRNAs, focusing mainly on inflammation and cell survival after ethanol/LPS treatment, and advances on the role of circulating miRNAs in human alcoholic disorders.